EVENT STUDY: TELAAH METODOLOGI DAN PENERAPANNYA DI BIDANG EKONOMI DAN KEUANGAN - ARIF BUDIARTO; MURTANTO (Jurnal Bisnis dan Akuntansi, 2002)
Event study methodology has been one of the most frequently used tools in financial research in recent years. In event studies, the objective is to examine the market's response to some well defined event through the observation of security prices around such event. Example of event, such as announcement of right issue, stock split, and accounting information. Event studies involve 5 steps: (1) identify the event of interest, (2) identify the time of parameter, (3) estimate the abnormal return, (4) organize and group the abnormal return, and (5) analyze the result. Event studies will continue making empirical contributions to the understanding of information and security price. This paper provides a review of the present state of knowledge and practice with respect to event study methodology. Many variations of this methodology are diccussed, as well as special issues and applications to research in capital market. Recommendations for implementing an event study also are provided.